2005
DOI: 10.2333/bhmk.32.95
|View full text |Cite
|
Sign up to set email alerts
|

A Multidimensional Scaling Model for Three-Way Data Analysis

Abstract: This article proposes a model that facilitates the analysis of triadic relationships among three objects. Recently, interest in studies of three-way data models has increased, and many significant contributions have been made in this area. However, one-mode, three-way models have yet to be considered. This study focuses on a onemode, three-way model in which three-way distances are explained as the subtraction of the smallest squared distance among the three squared distances from the sum of these squared dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Methods for analyzing this type of triadic distance data go back to Hayashi (1972). Representative methods in this category are , Daws (1996), De Rooij and, Gower and De Rooij (2003), Hayashi (1972Hayashi ( , 1989, Heiser and Bennani (1997), Joly and Le Calvé (1995), Nakayama (2005), and Nakayama and Okada (2011). These are descriptive MDS methods which assume certain symmetric, triadic distance models.…”
Section: Discussionmentioning
confidence: 99%
“…Methods for analyzing this type of triadic distance data go back to Hayashi (1972). Representative methods in this category are , Daws (1996), De Rooij and, Gower and De Rooij (2003), Hayashi (1972Hayashi ( , 1989, Heiser and Bennani (1997), Joly and Le Calvé (1995), Nakayama (2005), and Nakayama and Okada (2011). These are descriptive MDS methods which assume certain symmetric, triadic distance models.…”
Section: Discussionmentioning
confidence: 99%
“…Examples of functions that satisfy inequality (c4) can be found in Joly and Le Calvé (1995), Bennani-Dosse (1993), Heiser and Bennani (1997) and Nakayama (2005). However, it should be noted that, although there are many cases in which this three-way metric inequality is valid, the three-way models can be used regardless of the validity of the three-way axiom.…”
Section: Discussionmentioning
confidence: 99%
“…Daws (1996) incorporated three-way information in the analysis of free-sorting data. Methods for multi-way multidimensional scaling can be found in Cox et al (1991), Heiser and Bennani (1997), Gower and De Rooij (2003) and Nakayama (2005). Cox et al (1991), Diatta (2006) and Daws (1996) convincingly showed that multi-way dissimilarities may be used to detect possible higher-order relations between the objects.…”
Section: Theorem 1 (A2) + (A4) ⇒ (A1) (A3)mentioning
confidence: 99%